2015
DOI: 10.1021/ja511560b
|View full text |Cite
|
Sign up to set email alerts
|

Using Hollow Carbon Nanospheres as a Light-Induced Free Radical Generator To Overcome Chemotherapy Resistance

Abstract: Under evolutionary pressure from chemotherapy, cancer cells develop resistance characteristics such as a low redox state, which eventually leads to treatment failures. An attractive option for combatting resistance is producing a high concentration of produced free radicals in situ. Here, we report the production and use of dispersible hollow carbon nanospheres (HCSs) as a novel platform for delivering the drug doxorubicine (DOX) and generating additional cellular reactive oxygen species using near-infrared la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(122 citation statements)
references
References 67 publications
(107 reference statements)
3
119
0
Order By: Relevance
“…We found that the local mild thermal stimulus and the triggered generation of free radicals by laser treatment enhanced the expression of heat shock factor-1 (HSF-1), which depressed the activation of NF- κ B pathways (figure 4) [114]. Importantly, the NF- κ B pathway is well known to regulate drug resistance using high expression of pump proteins in the cell membrane and low sensitivity to toxic chemotherapeutic drugs [114, 123]. As a result, local NIR irradiation can successfully depress resistant pathways to overcome drug resistance.…”
Section: Interaction Of Au Nps With Cellsmentioning
confidence: 99%
“…We found that the local mild thermal stimulus and the triggered generation of free radicals by laser treatment enhanced the expression of heat shock factor-1 (HSF-1), which depressed the activation of NF- κ B pathways (figure 4) [114]. Importantly, the NF- κ B pathway is well known to regulate drug resistance using high expression of pump proteins in the cell membrane and low sensitivity to toxic chemotherapeutic drugs [114, 123]. As a result, local NIR irradiation can successfully depress resistant pathways to overcome drug resistance.…”
Section: Interaction Of Au Nps With Cellsmentioning
confidence: 99%
“…12,13 Comparatively, laser irradiation-assisted photothermal therapy (PTT) or photodynamic therapy (PDT) are non-invasive mode that can generate heats or free radicals at tumor site. [14][15][16] Photothermal therapy agents are capable of converting light energy into heat that causes a rise in the local temperature beyond 42 °C that consequently kill cancer cells. 17,18, 19 As a FDA-approved drug, indocyanine green (ICG) is attractive for localized hyperthermia that absorbs near infrared light (700-1000 nm) even in deep tissue 20,21 to generate heat.…”
Section: Introductionmentioning
confidence: 99%
“…[ 53 ] Compared with the most widely used carbon precursor for the HCS hosts (e.g., phenol formaldehyde resin, saccharide, and dopamine), polybenzoxazine (PB) has been largely overlooked although recent literature suggests that PB-based polymer is an interesting precursor for N-doped carbon nanostructures. [ 54,55 ] We demonstrate for the fi rst time that PB can be applied into the Stöber coating method for the templating synthesis of N-HCS with the controllable structure parameters.…”
mentioning
confidence: 97%